(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
Composition of fresh and frozen meat products, specially fat content, is one of the parameters that is usually taken into account for different purposes such as classification of fresh and frozen meat pieces for fresh consume as well as for processing, price fixation and adequacy for processing. That is the reason why some different non destructive methods are used to determine, at least approximately, the meat composition. Among them, we can go from visual methods to the more complex resonance imaging and computed tomography image analysis. The aim of this study was to use density measurement as a non destructive, easy and cheap method to classify fresh and frozen meat with a wide range of fat content. The obtained results showed that there is asignificant relationship between density and fat content of fresh and frozen meat.